Obesity in children with frequent relapse and steroid dependent nephrotic syndrome - Jeanne Vidianty; Sudung O. Pardede; Aryono Hendarto; Arwin A. P. Akib (Paediatrica Indonesiana, 2010)
Background Children \\lith frequent relapse and steroid dependent nephrotic syndrome (FRNS/SDNS) will experience frequent relapse v.ith many complications due to the disease and toxicity of steroid therapy. One of the most common complications is obesity which is associated \\lith significant health problems in childhood and important risk factor of adult morbidity and mortality. Objective To find out the prevalence of obesity in children 'With FRNS/SDNS.Methods A cross sectional study was conducted from November 2008 until March 2009. Data were collected from the medical records of children 'With FRNS/SDNS treated during the period of 2000-2008. Body weight, height and body fat mass measurement was performed on the subjects. The diagnosis of obesity was based on body mass index (BMI) and body fat mass measurement.Results Obesity was diagnosed in 10 of 43 children (23%). Most of them were 5􀀼9 years old (58%) 'With male􀀼predominance. Most patients (70%) had age of onset younger than 5 years. The median of total relapse was 7 (range 2􀀼24) and cumulative dose of prednisone was 12,240 (range 3,490 to 44,330) mg. Time since the last dose of prednisone until the study in majority was 0 to 6 months (53%). The prevalence of obesity based on BMI was 7%while based on body fat mass was 23 (el 95% 10 to 36) %. Conclusion The prevalence of obesity based on body fat mass was 23%. The median BMI of obese subjects is in the 90-95th percentile.